The role of HRD in CSR and sustainability: a content analysis of corporate responsibility reports. Issue 6 (24th April 2020) - Jang, Soebin; Ardichvili, Alexandre
Abstract : Purpose: This study aims to examine the role of human resource development (HRD) in corporate social responsibility (CSR) and sustainability initiatives of multinational companies (MNCs). Design/methodology/approach: The authors analyze contents of corporate responsibility (CR) reports disclosed by 23 MNCs from Europe, Asia and North America to examine HRD's contribution to CSR and sustainability, with particular attention to long-term human development and organization development. Findings: The analysis of CR reports indicates that HRD is perceived as playing a role in the following areas: diversity, equity and inclusion; community engagement; work–life balance; employee long-term growth and development; performance management; business ethics and ethical culture; and raising CSR awareness. In all areas, HRD was identified as playing a significant role in supporting companies' CSR agendas. Originality/value: This study extends research on the intersection of HR, CSR and sustainability and provides evidence of HRD's important contributions to CSR and sustainability.